The effect of training on some physiological variables in a modern basketball game (Journal of the College of Basic Education, 2023)
Sports training is a well-studied, organized process based on scientific foundations.the player to the highest possible level of regular and coordinated movements to ensure a high performance speed and thatThrough strong and rapid reactions within the available physiological limits.The amazing development that appears in the technical performance and the high numerical level is onlyA reflection of what was relied upon in terms of hypotheses and basic scientific facts that could be harnessed and adapted to suitThe field of sports training, training planning, rehabilitation and fitness operations to overcome the emergence of fatigueAnd fatigue during the actual performance of the activity to achieve the desired progress on the various sports levels (3).From the biological point of view, training is a process of familiarizing body systems with different types of organisms.Physical loads all lead to morphological and physiological changes that result in an increase inBody efficiency and the ability to face the functional and structural requirements of any type of activitysports (2).Muhammad Sobhi Abdel Hamid and Muhammad Muhammad Abdel Aal (6) agreed on the importance of the vital roleWhich is played by the physical load because it provides the coach with basic information in order to form the load and distribute itTo ensure the progress and upgrading of the player's physiological ability for the purpose of achieving complete conditioning of the body's systems.different types under the influence of sports training (6).The game of basketball has a special character that makes it different from other games.Because of the nature of modern performance in the game, which has been developed in the recent era, and the huge amount it requires.for the training and match campaigns in terms of intensity and size, as the game witnessed a great development, whetherby defense or attack, which led to reaching high levels of technical and tactical performance incompetition (7).In recent years, technical and legal amendments have been made in the international law of basketball.Consequently, there is a change in the style of playing and training. Therefore, the importance of research comes in knowing the effect ofThe modern training method of this game and its pattern on some physiological changes within the framework ofNew amendments to the laws of the game.